2022
DOI: 10.1021/acsomega.1c05750
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Crystal Structure, DNA and HSA Interactions, and Anticancer Activity of a Mononuclear Cu(II) Complex with a Schiff Base Ligand Containing a Thiadiazoline Moiety

Abstract: A mononuclear Cu­(II) complex [Cu­(HL)­(o-phen)]·H2O (1) [H3L =, o-phen = 1,10-phenanthroline] was isolated from methanol, and its X-ray single-crystal structure was determined. Frozen glass X-band EPR of 1 in dimethylformamide (DMF) at LNT showed a spectrum that is characteristic of a monomeric tetragonal character with g ∥ = 2.164, g ⊥ = 2.087, A ∥ = 19.08 mT, and A ⊥ ≤ 4 mT. Electronic spectroscopic studies using calf thymus DNA (CT-DNA) showed strong binding affinity of 1 as reflected from its intrinsic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 88 publications
(159 reference statements)
1
19
0
Order By: Relevance
“…Flow cytometry was used to analyze the PI-stained cell population in different cell cycle stages. , A typical cell cycle consists of four phases, that is, G1, S, G2, and M. Exposure of HeLa cells to complex 1 led to an increase in the cell population in the S phase, wherein DNA gets replicated. This population increase was prominent, and a dose-dependent increase with complex 1 concentration was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry was used to analyze the PI-stained cell population in different cell cycle stages. , A typical cell cycle consists of four phases, that is, G1, S, G2, and M. Exposure of HeLa cells to complex 1 led to an increase in the cell population in the S phase, wherein DNA gets replicated. This population increase was prominent, and a dose-dependent increase with complex 1 concentration was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA affinities of the compounds are evaluated using absorbance titration studies, [57] and it is proposed that the complexes’ DNA binding is due to the intercalative mode, which is further investigated using EB quenching assays [58] . Using agarose gel electrophoresis and a 365 nm exposure, we investigated photoinduced DNA cleavage [59] .…”
Section: Dna Enzymes and Proteins As Drug Targetmentioning
confidence: 99%
“…These results indicated that the complexes could interact with CT-DNA. [26][27][28] The different binding forces were due to the difference of the N^N ligands, in which the NH group of HPB is more helpful for the interaction between complex 1 and DNA.…”
Section: Dna-binding Experimentsmentioning
confidence: 99%